Revitalisasi Fungsi Edukatif Majelis Taklim Sebagai Upaya Penguatan Literasi Hukum Keluarga Islam di Kecamatan Barumun - Nasution, Nur Hakimah Akhirani; Pane, Erwin Hamonangan (Yayasan Perguruan Kampus, 2026)
This community service program aimed to revitalize the educational function of majelis taklim as an effort to strengthen Islamic family law literacy among the community in Kecamatan Barumun. The main problems faced by the community were the low level of understanding regarding Islamic family law, particularly related to the rights and obligations of husbands and wives, marriage administration, family conflict resolution, protection of women and children, and inheritance distribution according to Islamic law. On the other hand, majelis taklim, which has traditionally served as a center for religious education in society, has not yet optimally carried out its educational function in the field of Islamic family law. The implementation method employed a participatory community empowerment approach through stages of socialization, needs identification, training, mentoring, monitoring, and evaluation. Educational activities were conducted through interactive lectures, group discussions, family case simulations, and community-based mentoring. The results showed an increase in community understanding of Islamic family law. Before the program implementation, 68% of participants were categorized as having a low level of understanding, while after the activities, 74% of participants reached a good level of understanding. Furthermore, the program succeeded in strengthening the educational function of majelis taklim through the development of thematic studies on Islamic family law and the application of more participatory learning methods. This community service activity demonstrates that majelis taklim has strategic potential as a community-based socio-religious educational medium in improving Islamic family law literacy and strengthening family resilience in rural communities.